Chronic pain in narcolepsy type 1 and type 2 – an underestimated reality. (19th June 2018) - Cremaschi, Renata C.; Hirotsu, Camila; Tufik, Sergio; Coelho, Fernando M.
Summary: Narcolepsy is a rare sleep disorder classified in types 1 and 2. The co‐morbidities of narcolepsy type 1, with hypocretin‐1 deficiency, are established. Hypocretin‐1 in the central and peripheral nervous systems regulates nociception and pain. However, the patients with narcolepsy type 2 have similar excessive daytime sleepiness and co‐morbidities without elucidation. The objective of the study was to determine the frequency and the characteristic of chronic pain according to the type of narcolepsy. We also investigated the effect of the interaction between the nutritional status and the type of narcolepsy. It was a cross‐sectional study using self‐administered questionnaires. Patients with narcolepsy (33 type 1 and 33 type 2), from Universidade Federal de São Paulo, Brazil, matched by age and gender to 33 control subjects were included. Both types of narcolepsy presented a high frequency of chronic pain (84.84% type 1 versus 75.75% type 2), with indistinct pain characteristics between them. The odds ratio was 20.8 in type 1 and 11.6 in type 2, compared with controls. Obese individuals with narcolepsy type 1 and type 2 did not present a significant difference in pain intensity, compared with obese controls. Patients with narcolepsy type 1 and type 2 were associated with a high frequency of chronic pain. Chronic pain emerged as a co‐morbidity never reported before in type 2. Depression possibly influences pain perception in these patients. Obesity might play a role in pain intensity in narcolepsy. The treatment of narcolepsy should take account of chronic pain, depression and obesity management.